Enzyme Design from the Bottom Up: An Active Nickel Electrocatalyst with a Structured Peptide Outer Coordination Sphere. Issue 6 (17th January 2014) - Reback, Matthew L.; Buchko, Garry W.; Kier, Brandon L.; Ginovska‐Pangovska, Bojana; Xiong, Yijia; Lense, Sheri; Hou, Jianbo; Roberts, John A. S.; Sorensen, Christina M.; Raugei, Simone; Squier, Thomas C.; Shaw, Wendy J.
Abstract Catalytic, peptide‐containing metal complexes with a well‐defined peptide structure have the potential to enhance molecular catalysts through an enzyme‐like outer coordination sphere. Here, we report the synthesis and characterization of an active, peptide‐based metal complex built upon the well‐characterized hydrogen production catalyst [Ni(PPh2NPh)2]2+ (PPh2NPh=1, 3, 6‐triphenyl‐1‐aza‐3, 6‐diphosphacycloheptane). The incorporated peptide maintains its β‐hairpin structure when appended to the metal core, and the electrocatalytic activity of the peptide‐based metal complex (≈100, 000 s−1) is enhanced compared to the parent complex ([Ni(PPh2NAPPA)2]2+; ≈50, 500 s‐1). The combination of an active molecular catalyst with a structured peptide provides a scaffold that permits the incorporation of features of an enzyme‐like outer‐coordination sphere necessary to create molecular electrocatalysts with enhanced functionality.